A monk swimming : a memoir - McCourt, Malachy, 1931- (New York : Hyperion, 1998)
In 1952, travelling steerage, Malachy McCourt left a childhood of poverty in Limerick, Ireland, heading for the promise of America. This is the story of what he brought with him, and what he thought he left behind. Armed with savage humor and a gift for storytelling, fueled by rage and the desire never to go hungry again, he ran from memories of a drunken, vanished father and the humiliations of Angela, his mother. He arrived in a New York reminiscent of a Damon Runyon saga-- a dark, glittering place, with saloons on every corner, and a new story waiting every night. Larger than life, a world-class drinker, McCourt carved out a place for himself: in the saloons, as the first celebrity bartender, mixing with socialites, writers, and movie stars; on stage, performing the works of James Joyce and Brendan Behan; and on television, where the tales he spun made him a Tonight Show regular. He had money and women and, eventually, children of his own; and that's when he found he had not left his memories as far behind as he had thought. From the notorious Tombs prison of New York City, to poolside arrests in Beverly Hills; in the company of gold-smugglers in Zurich and whores in Calcutta; from Paris, to Rome, and to Limerick once more, McCourt fled again, until he had no choice but to stop and turn and face his past
Keywords: McCourt, Malachy, -- 1931-; Irish Americans -- New York (State) -- New York -- Biography; New York (N.Y.) -- Biography